Penerapan Model Pembelajaran Problem Based Learning Dalam Meningkatkan Hasil Belajar Pada Mata Pelajaran PAI di SDN 19 Parit Lubang - Rosnita, Rosnita (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
Education has an important role in shaping the condition of a country, both in economic and social aspects. One of the subjects that has a big role is Islamic Religious Education, which aims to develop students' potential as a whole. However, in practice, the learning methods used still tend to be conventional and less able to increase student involvement, especially in Islamic Religious Education classes. Therefore, this study aims to improve the learning outcomes of grade V students at SDN 19 Parit Lubang through the application of the Problem Based Learning model on the material of Living Peacefully in Togetherness. This research focuses on efforts to improve student learning outcomes through a more interactive and fun learning model. The results showed that the application of Problem Based Learning can significantly improve student learning outcomes, with an increase in active participation and student motivation in participating in learning.